The consequences analysis of fire and explosion scenario using ALOHA software on loading area at Company X in 2020 - Rizky, Salsabilla Anisah (Health Safety Environment, 2021)
Fire can obliterate the company workers end products in the fastest time, resulting in financial losses with the emergence of the potential hazard. If this happened in the Loading area, it could cause a delay to the distribution departure schedule all over Java. This study aimed to analyze fire and explosion scenarios that occur due to the diesel storage tank leakage in the Loading area at Company X with Area Location of Hazardous Armosphere (ALOHA) software. This study used a descriptive study design. The technique is data collected with literature review, direct observation, and institution data analysis. Furthermore, the data were collected also input to ALOHA software such as chemical data of isooctane, atmospheric data, and source strength to the worst scenario of leakage. That the risk area and population at risk are obtained. Threat zone from the worst scenario such as gas dispersion is 79 m, pool fire is 62 m, Boiling Liquid Expanding Vapor Explosion (BLEVE) is 457 m, and Vapor is none from the center of the fire. Furthermore, a safe distance from the diesel storage tank is as far as 457 m. The total population at risk was 39 workers in Company X and 43,846 population in Tanjung Priok Sub-District. The suggestion given is the institution manager needs to carry out socialization about hazard and impact related to fire and explosion, also the counter measures with workers and public around in loss prevention.Keywords:  ALOHA - Threat zone - Safe distance - Diesel storage tank